2007
DOI: 10.1186/1751-0759-1-24
|View full text |Cite
|
Sign up to set email alerts
|

Altered autonomic nervous system activity as a potential etiological factor of premenstrual syndrome and premenstrual dysphoric disorder

Abstract: Background: Premenstrual syndrome (PMS) encompasses a wide variety of cyclic and recurrent physical, emotional, and behavioral symptoms occurring during the late luteal phase of the menstrual cycle and abating shortly following the beginning of menses. Although PMS is widely recognized, its etiopathogenesis is not yet understood. The present study investigates whether the activity of the autonomic nervous system, which plays a vital role in orchestrating physiological homeostasis within the human body, is alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
2
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 33 publications
3
60
2
8
Order By: Relevance
“…Both E1 and PdG were indexed to creatinine (Cr) excretion. 17,19,25,28 All measurements were taken between 11:00 and 15:00, in consideration of the circadian rhythm of salivary stress markers. 29 We carried this out in a temperature-controlled (25°C), quiet, comfortable room, with minimization of arousal stimuli.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both E1 and PdG were indexed to creatinine (Cr) excretion. 17,19,25,28 All measurements were taken between 11:00 and 15:00, in consideration of the circadian rhythm of salivary stress markers. 29 We carried this out in a temperature-controlled (25°C), quiet, comfortable room, with minimization of arousal stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…Menstrual cycle-related discomfort, such as premenstrual syndrome and premenstrual dysphoric disorder, influences the autonomic nervous system. 17,[19][20][21] However, scores from the menstrual distress questionnaire 22 the participants had answered in the follicular (the fifth to the 11th day from the first day of menstruation) and the late-luteal phase (within 7 days before the next menstruation) revealed that none of the participants had premenstrual disorders. The medical examination and interview further clarified that no participants had any other gynecologic or psychiatric disorders.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frekuensi nadi menurun pada fase luteal dibandingkan pada fase folicullar. Penelitian matsumoto menunjukkan bahwa aktifitas sistem syaraf parasimpatis menurun pada fase luteal dibandingkan pada fase folikular (2). L a t i h a n y o g a s e c a r a t e r a t u r d a p a t menyeimbangkan sistem saraf otonom, sehingga tubuh menjadi lebih relaks dan pengeluaran hormonhormon yang berperan dalam peningkatan tekanan darah, seperti hormon adrenalin dan eprineprin lebih terkontrol.…”
Section: Hasil Dan Bahasan Pengaruh Yoga Terhadap Tekanan Sistolik Dunclassified
“…Akibat fluktuasi hormon fisiologis pada perempuan yang terjadi secara regular dan siklik. Beberapa penelitian menyebutkan bahwa perubahan fungsi system syaraf otonom selama fase luteal berhubungan dengan kejadian gejala psikosomatik yang muncul pada fase menstruasi, hal ini dapat berdampak terhadap produktifitas perempuan pada saat menstruasi (2). Berdasarkan data Survei Ketenagakerjaan Nasional (Sukernas) tahun 2011, Tingkat Partisipasi Angkatan Kerja (TPAK) perempuan sekitar 52,44%, jika dibandingkan dengan TPAK laki-laki sebesar 84,30% dapat dikatakan rendah, namun dengan bertambah lamanya pendidikan, kebutuhan sosial dan ekonomi keluarga mendorong perempuan untuk dapat berpartisipasi sebagai tenaga kerja.…”
unclassified